COMPUTATIONAL THINKING IN MATHEMATICS EDUCATION: EXAMINING BEBRAS'S USE AS A LEARNING TOOL FOR 2D SHAPES - Yeni Fitriya; Maylita Dwi Putri; M. Miftaqul Miftah Lutfi (AFHAM : Jurnal Pendidikan dan Keguruan, 2026)
Educational developments in the 21st century call for the integration of computational thinking into learning to develop students’ logical, systematic, and problem-solving skills. However, mathematics instruction on two-dimensional (2D) shapes still tends to be oriented toward a procedural approach, so students’ computational thinking skills have not developed optimally. This study aims to analyze the use of Bebras as a learning tool to enhance students’ computational thinking skills in the context of two-dimensional shapes. The study employs a quantitative approach with a pretest–posttest design. The research subjects consisted of 32 upper-grade elementary school students. Data collection techniques included tests, observations, and student response questionnaires. Data were analyzed using quantitative descriptive analysis to determine changes in computational thinking skills across the indicators of problem decomposition, pattern recognition, abstraction, and algorithm design. The results indicate that the use of Bebras has a positive impact on improving students’ computational thinking skills. The students’ average score increased from 61.4 on the pretest to 84.2 on the posttest. Improvements were observed across all computational thinking indicators, with the highest increase in the pattern recognition aspect. In addition, the results of the observations showed an increase in student engagement and learning activity, while the questionnaire results indicated that the majority of students responded positively to the use of Bebras in mathematics instruction. Students found the lessons to be more engaging, interactive, and helpful in gaining a deeper understanding of two-dimensional geometric concepts. Based on the research results, it can be concluded that Bebras is effective as a mathematics learning tool for improving computational thinking skills in two-dimensional plane figures. The integration of Bebras into mathematics instruction has the potential to become a 21st-century learning innovation that supports the development of students’ higher-order thinking skills, problem-solving abilities, and understanding of geometric concepts.